IDENTIFIKASI ATRIBUT SENSORI WHITE STOCK DENGAN DIFFERENCE TEST - Melati Pratama, melati08 (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2024)
White stock was the liquid that come from meat or bone decoction. The principal of making white stock was produce extract that had in bone. The producing white stock was various, but it was predictably can effect sensory attribute (color, aroma taste). The subjective of this research was to identified sensory attribute (color, aroma, taste) white stock by different cooking method like Sample 1 (sequence bone-water) and Sample 2 (sequence water-bone). Sampel was tested use organoleptic difference test. The data was analyzed by binomial distribution table at 95% by 25 untrained panelists. The result show that, both of cooking method such as sequence bone-water and water bone gave significant effect to sensory (color, aroma and taste). Sample 1 (sequence bone-water) and Sample 2 (sequence water-bone) had color, aroma and taste that difference. The Sample 2 (sequence water-bone) had color, aroma and taste was thicker than Sampel 1 (sequence bone – water).